Perilaku pencarian informasi beauty vlogger di wilayah Kabupaten Trenggalek untuk memenuhi kebutuhan informasi pada proses pembuatan konten video - Kholidz Wildan Wafi; Darisy Syafaah (S1 Ilmu Perpustakaan dan Informasi Islam FTK UIN Antasari Banjarmasin, 2023)
The emergence of beauty vloggers is currently a trend in the world of beauty because they can influence skincare or make-up products through video content that is shared. This study intends to find out the information seeking behavior of beauty vloggers in the Trenggalek Regency area to meet information needs in the process of creating video content, as well as the obstacles faced by beauty vloggers in searching for information as an effort to meet information needs in the process of creating video content and how to overcome them. The type of approach used in this study is a qualitative descriptive approach. The data collection technique used was interviews with three beauty vloggers, observation and documentation. As well as data analysis used, namely data reduction, data presentation and drawing conclusions. The results of the study show that the information seeking behavior model used by beauty vloggers in the Trenggalek Regency area is in accordance with the theory put forward by David Ellis which is divided into 8 stages including Starting, Chaining, Browsing, Differenting, Monitoring, Extracting, Verifying, Ending via whatsapp, tick tock, instagram and google. The results of the study also show the obstacles faced by beauty vloggers which are divided into 2 factors including internal factors in the form of lack of information availability and external factors in the form of inadequate internet networks. However, the constraints from these internal factors can be handled by re-searching information, while external factors can be handled by postponing information search activities and looking for a place that has network access that supports it.